NOBCChE News, Volume 18, Number 3 (National Organization for Black Chemists and Chemical Engineers, 1997)
Winter 1997 issue of NOBCChE News.
Keywords: National Organization for Black Chemists and Chemical Engineers; Chemists; Chemical engineers; African American chemists; African American engineers; Newsletters; Periodicals; Scientists, Black; African American scientists